OPTIMALISASI PENGELOLAAN PAJAK REKLAME SEBAGAI SUMBER PENDAPATAN DAERAH DI KOTA SEMARANG - Astuti, Puji; Adhi, Suwanto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2007)
Autonomy and automoney ate the two things that couldn't be separated. For reaching autonomy effectiveness, local goverment should be supported by finance capacity. Within finance adequacy, local goverment, especially Cities and Regencies would have opportunity to mett the public services without interference by central goverment.According Tax Regulation Number 34 Year of 2000, Cities could collecting revenue from taxes as a local resources, the one is tax of advertisement. As a city with great of economic growth, advertisement could be the one of potential local resources. Almost strategic corner in all around of Semarang have changed as a centre of advertisement board. However, advertisement have not been optimum collected, and for this reason advertisement still having small contribution as a local revenue in Semarang City.